If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -3(x + 10) = -3 Reorder the terms: 6 + -3(10 + x) = -3 6 + (10 * -3 + x * -3) = -3 6 + (-30 + -3x) = -3 Combine like terms: 6 + -30 = -24 -24 + -3x = -3 Solving -24 + -3x = -3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + -3x = -3 + 24 Combine like terms: -24 + 24 = 0 0 + -3x = -3 + 24 -3x = -3 + 24 Combine like terms: -3 + 24 = 21 -3x = 21 Divide each side by '-3'. x = -7 Simplifying x = -7
| 4x-4+10x-15= | | 3x+8=-14-8x | | 2x+8=92-8x | | 2x+10=90-6 | | 162-3x=24x+24 | | 4x-36=2x+10 | | 5x+33=7x+13 | | 6-8x=94-36x | | 29+x=10 | | x+42=41 | | 6-8x=94-39x | | 5x-17=23 | | a-10=27 | | k+3=21 | | n-34=-23 | | 8x+18=5x+6 | | 10=x+17+2x+16 | | y-41=112 | | v+36=85 | | b+8=-25 | | 6x+18=5x+7 | | 6y^2=11y+7 | | 14+y=67 | | 9x+15=6x+57 | | 14+y= | | 2x-5yi=12+15i | | 10-10x=18-17x | | 60-3x=6x+19 | | 55-4x=32x+15 | | (x-5)=8 | | 12+6=9x+24 | | 4=n-(-3) |